Mammalian Transient Receptor Potential (TRP) Cation Channels: Volume II - Nilius, Bernd 1945-; Flockerzi, Veit (Handbook of experimental pharmacology, 2014)
In this fast moving field the main goal of this volume is to provide up-to-date information on the molecular and functional properties and pharmacology of mammalian TRP channels. Leading experts in the field describe properties of a single TRP protein/channel or portray more general principles of TRP function and important pathological situations linked to mutations of TRP genes or their altered expression. Thereby this volume on Transient Receptor Potential (TRP) Channels provides valuable information for readers with different expectations and backgrounds, for those who are approaching this field of research as well as for those wanting to make a trip to TRPs